Electrical characterization of capacitively-coupled radio-frequency discharges in hydrogen - Marques, L. (2007)
This work presents modeling and experimental results for the electrical characterization of capacitively-coupled radio-frequency discharges in hydrogen. A two-dimensional, time-dependent fluid model is used to describe the dynamics of electrons and positive ions H+, H2+, and H3+at different frequencies (13.56–80 MHz), pressures (0.2–1 Torr), and rf applied voltages (50–800 V). The current-voltage relationship is reported and found in good qualitative agreement with experiment. The distribution, between electrons and ions, of the electrical power coupled to the plasma is analyzed. An investigation of the scaling laws for several important plasma parameters is also carried out.